An object kinetic Monte Carlo model for the microstructure evolution of neutron‐irradiated reactor pressure vessel steels. Issue 11 (7th September 2016) - Messina, Luca; Chiapetto, Monica; Olsson, Pär; Becquart, Charlotte S.; Malerba, Lorenzo
Abstract : This work presents a full object kinetic Monte Carlo framework for the simulation of the microstructure evolution of reactor pressure vessel (RPV) steels. The model pursues a "gray‐alloy" approach, where the effect of solute atoms is seen exclusively as a reduction of the mobility of defect clusters. The same set of parameters yields a satisfactory evolution for two different types of alloys, in very different irradiation conditions: an Fe–C–MnNi model alloy (high flux) and a high‐Mn, high‐Ni RPV steel (low flux). A satisfactory match with the experimental characterizations is obtained only if assuming a substantial immobilization of vacancy clusters due to solute atoms, which is here verified by means of independent atomistic kinetic Monte Carlo simulations. The microstructure evolution of the two alloys is strongly affected by the dose rate; a predominance of single defects and small defect clusters is observed at low dose rates, whereas larger defect clusters appear at high dose rates. In both cases, the predicted density of interstitial loops matches the experimental solute‐cluster density, suggesting that the MnNi‐rich nanofeatures might form as a consequence of solute enrichment on immobilized small interstitial loops, which are invisible to the electron microscope.